2018
DOI: 10.23913/rics.v7i13.61
|View full text |Cite
|
Sign up to set email alerts
|

Percepción materna y estado de peso del hijo escolar en una comunidad rural / Maternal perception of the state of weight of the schoolchildren in a rural community

Abstract: Percepción materna y estado de peso del hijo escolar en una comunidad rural ResumenLa percepción materna es el reconocimiento y la discriminación de la madre respecto al peso del hijo, considerándolo como un niño con sobrepeso, con desnutrición o sano; las madres con una percepción inadecuada refieren que el peso del hijo no es un problema de salud y, en consecuencia, evitan la identificación oportuna de alteraciones nutricionales que afectan su crecimiento y desarrollo. El objetivo de esta investigación fue d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Validated in the study “Body Figure Perceptions and Preferences Among Preadolescent Children,” this scale achieved a test–retest reliability level of 0.91 ( 29 ). This instrument has been employed in Latin American child populations aged 6 to 10, sharing characteristics similar to our study population ( 14 ). The scale categorizes BMI/Age using seven anatomical silhouettes for both males and females, depicting the child’s physical appearance.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Validated in the study “Body Figure Perceptions and Preferences Among Preadolescent Children,” this scale achieved a test–retest reliability level of 0.91 ( 29 ). This instrument has been employed in Latin American child populations aged 6 to 10, sharing characteristics similar to our study population ( 14 ). The scale categorizes BMI/Age using seven anatomical silhouettes for both males and females, depicting the child’s physical appearance.…”
Section: Methodsmentioning
confidence: 99%
“…Mothers, traditionally the primary caregivers, significantly influence their children's dietary habits (12,13). However, studies have shown that many mothers with overweight or obese children tend to underestimate their weight, thus reducing the likelihood of taking preventive actions and engaging in weight-loss interventions for their children (14)(15)(16)(17)(18). This misperception was highlighted by Trejo et al (19), who found that most Peruvian parents with overweight or obese children did not accurately perceive their children's weight (19).…”
Section: Introductionmentioning
confidence: 99%